2008
DOI: 10.1200/jco.2008.17.7162
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Addition to Supportive Care Improves Survival in Advanced Non–Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis of Individual Patient Data From 16 Randomized Controlled Trials

Abstract: A B S T R A C T PurposeSince our individual patient data (IPD) meta-analysis (MA) of supportive care and chemotherapy for non-small-cell lung cancer (NSCLC), published in 1995, many trials have been completed. An updated, IPD MA has been carried out to assess newer regimens and determine conclusively the effect of chemotherapy. MethodsSystematic searches for randomized controlled trials (RCTs) were undertaken, followed by central collection, checking, and reanalysis of updated IPD. Results from RCTs were combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
167
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(169 citation statements)
references
References 33 publications
0
167
0
2
Order By: Relevance
“…Standard treatment of advanced disease is based on the combination of a platinum-derivative with a second drug such as gemcitabine, paclitaxel, pemetrexed, docetaxel or vinorelbine. [1][2][3][4][5] Advanced NSCLC patients however, despite the treatment, have a median overall survival (OS) of about 10 mo. 6 More recently, the efficacy of standard combination chemotherapy has been improved by the introduction Bevacizumab is a humanized anti-VeGF monoclonal antibody able to produce clinical benefit in advanced non-squamous non-small cell lung cancer (nsCLC) patients when combined to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Standard treatment of advanced disease is based on the combination of a platinum-derivative with a second drug such as gemcitabine, paclitaxel, pemetrexed, docetaxel or vinorelbine. [1][2][3][4][5] Advanced NSCLC patients however, despite the treatment, have a median overall survival (OS) of about 10 mo. 6 More recently, the efficacy of standard combination chemotherapy has been improved by the introduction Bevacizumab is a humanized anti-VeGF monoclonal antibody able to produce clinical benefit in advanced non-squamous non-small cell lung cancer (nsCLC) patients when combined to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…66,67 Recent data from a phase III trial suggest that cisplatin plus pemetrexed has a survival advantage over cisplatin plus gemcitabine for NSCLC with non-squamous histology. 68 Second-line chemotherapy is increasingly used for patients of good performance status.…”
Section: Advanced Nsclcmentioning
confidence: 99%
“…This meta-analysis showed that chemotherapy significantly improved patients’ quality of life (QoL) and median overall survival (OS) by 1.5 months as compared to best supportive care (BSC). More recently, a second meta-analysis has been published including individual data from 2,714 patients treated also with third-generation drugs in 16 randomized clinical trials confirming a survival advantage of 1.5 months for chemotherapy as compared to BSC alone [5]. In the last two decades several randomized studies compared third-generation platinum-based doublets showing that front-line regimens have reached a plateau for clinical efficacy differing mainly for their toxicity profiles and convenience [6].…”
Section: Introductionmentioning
confidence: 99%